2019
DOI: 10.1093/cid/ciz756
|View full text |Cite
|
Sign up to set email alerts
|

Early and Successful Combination Antiretroviral Therapy Normalizes Survival Time in Patients Coinfected With Human Immunodeficiency Virus and Human T-cell Lymphotrophic Virus Type 1

Abstract: Background Coinfection with human T-cell lymphotrophic virus type 1 (HTLV-1) is associated with shorter survival for adults and children infected with human immunodeficiency virus (HIV), although the reasons remain a matter of debate. We evaluated the factors associated with survival time in a large cohort of HIV/HTLV-1–coinfected and HIV-monoinfected individuals on combination antiretroviral therapy (cART). Methods In a nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
5
18
0
Order By: Relevance
“…HTLV-1/HIV coinfected individuals in our cohort displayed fourfold higher mortality rates (2.6 per 100 person-years) as compared to recent data from an HIV cohort also located in metropolitan Sao Paulo (0.6 per 100 person-years) [36]. These mortality rates are strikingly similar to a recent publication comparing HTLV-1/HIV-1 coinfected patients (3.0 per 100 person-years) with HIV monoinfected patients (1.3 per 100 person-years) in Salvador-Bahia, Northeast Brazil [13]. However, Brites et al demonstrated that the decreased survival observed in HTLV-1/HIV-1 coinfected patients was normalized in those with early and successful ART [13].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…HTLV-1/HIV coinfected individuals in our cohort displayed fourfold higher mortality rates (2.6 per 100 person-years) as compared to recent data from an HIV cohort also located in metropolitan Sao Paulo (0.6 per 100 person-years) [36]. These mortality rates are strikingly similar to a recent publication comparing HTLV-1/HIV-1 coinfected patients (3.0 per 100 person-years) with HIV monoinfected patients (1.3 per 100 person-years) in Salvador-Bahia, Northeast Brazil [13]. However, Brites et al demonstrated that the decreased survival observed in HTLV-1/HIV-1 coinfected patients was normalized in those with early and successful ART [13].…”
Section: Discussionsupporting
confidence: 81%
“…The incidence of ATLL and HAM/TSP varies from 0.5% to 10% among HTLV-1 infected subjects, increasing morbidity and mortality rates [9] Additionally, treatment of coinfections, such as HIV and HCV, can be delayed due to HTLV-1 promoting an inefficacious increase in CD4+ cells, leading to a delay in antiretroviral therapy (ART) initiation and, possibly, inefficacious HCV clearance [10][11][12][13]. In endemic countries, parasitic coinfection with Strongyloides stercoralis also increases morbidity and mortality [12].…”
Section: Introductionmentioning
confidence: 99%
“…These mortality rates are strikingly similar to a recent publication comparing HTLV-1/HIV co-infected patients (3.0 per 100 person-years) with HIV monoinfected patients (1.3 per 100 person-years) in Salvador-Bahia, Northeast Brazil [17]. However, Brites et al demonstrated that the decreased survival observed in HTLV-1/HIV co-infected patients was normalized in those with early and successful ART [17].…”
Section: Discussionsupporting
confidence: 86%
“…HTLV-1/HIV co-infected individuals in our cohort displayed fourfold higher mortality rates (2.6 per 100 person-years) as compared to recent data from an HIV cohort also located in metropolitan Sao Paulo (0.6 per 100 person-years [40]. These mortality rates are strikingly similar to a recent publication comparing HTLV-1/HIV co-infected patients (3.0 per 100 person-years) with HIV monoinfected patients (1.3 per 100 person-years) in Salvador-Bahia, Northeast Brazil [17]. However, Brites et al demonstrated that the decreased survival observed in HTLV-1/HIV co-infected patients was normalized in those with early and successful ART [17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation